Swine Granulosa Cells Show Typical Endothelial Cell Characteristics. (May 2016) - Basini, Giuseppina; Falasconi, Irene; Bussolati, Simona; Grolli, Stefano; Di Lecce, Rosanna; Grasselli, Francesca
Granulosa cells, which belong to the somatic compartment of the ovarian follicle, are actively involved as endocrine cells in follicle growth. Recently, it has been proposed that these cells are not terminally differentiated and possess multipotency. Therefore, we cultured swine granulosa cells in specific endothelial cell culture medium (EBM-2), and phenotypic and functional characteristics of endothelial cells were assessed. The collected data suggest that these endocrine cells can also behave as endothelial cells, therefore potentially contributing to follicular angiogenesis, a crucial process in follicle growth and selection.